Problems and Prospects of Molecular Psychogenetics in the Study of Transsexsualism - Zhukovskii, A. O.; Kremenitskaya, S. A.; Solovieva, N. V.; Ryskov, A. P.; Vasilyev, V. A. (Molecular biology (New York), 2025)
The etiology of transsexualism (TS) remains unknown today because the disease is multifactorial and is caused by a set of factors, including those affecting sexual differentiation of brain tissue during fetal development. Sexual differentiation of the brain has been shown to occur at a much later developmental stage than sexual differentiation of the genitals, and the two processes are regulated independently of each other. Various sexual characteristics, such as gender identity (self-identification of oneself as male or female) and sexual orientation (heterosexuality, homosexuality, or bisexuality), as well as risks of developing neuropsychiatric disorders, are programmed in the brain at an early developmental stage. The structure of certain brain areas in transsexual individuals has been found to differ from that in cisgender men and women and is close, although not identical, to that in humans of the opposite anatomical and genetic sex. Various effects of physiologically active substances on the developing brain have been shown to result in irreversible or partly reversible modification of its neurochemical systems. Family studies have confirmed the role of genetic factors in gender identity disorders. The review provides a detailed analysis of the known loci of candidate genes presumably associated with TS. Both positive and negative correlations with TS have been revealed for most candidate genes, while only negative correlations are known for other markers. The inconsistency of the research results may be due to several factors, including “blurred” samples of transsexuals, the choice of neutral markers lacking the functionally significant polymorphisms that affect their expression and functionality, etc. The review considers the current data on the problem of TS and outlines the possible prospects for further research of the phenomenon at the genetic level with the aim of using the results to verify the diagnosis.